(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
It gives direction tocorporate values, corporate culture, corporate goals, and corporate missions.Under this broad corporate strategy there are typically business-levelcompetitive strategies and functional unit strategies. Refers to theoverarching strategy of the diversified firm. Such a corporate strategy answersthe questions of "which businesses should we be in?" and "howdoes being in these businesses create synergy and/or add to the competitiveadvantage of the corporation as a whole?" Business strategy refers tothe aggregated strategies of single business firm or a strategic business unit(SBU) in a diversified corporation. According to Michael Porter, a firmmust formulate a business strategy that incorporates eithercost leadership,differentiation, or focus to achieve a sustainable competitive advantage andlong-term success. These three rules are also known as Porter’s three genericStrategies; this concept can be applied to any size or form of business. Porterconsidered this concept as tradeoff strategy and argued that a person orcompany must only choose ONE strategy or risk having no strategy at all.